Enhanced photoelectrochemical performance of defect-rich ReS2 nanosheets in visible-light assisted hydrogen generation. (April 2018) - Huang, Jianwen; Gao, Haigen; Xia, Yufei; Sun, Yinghui; Xiong, Jie; Li, Yanrong; Cong, Shan; Guo, Jun; Du, Shiyu; Zou, Guifu
Abstract: Defect introduction is one of the most important motivations to produce highly efficient electrocatalyst in the field of water splitting. Here we report the visible-light enhanced photoelectrochemical performance derived from defect-rich ReS2 nanosheets with high activity towards hydrogen generation from water. After continuous pre-electrolysis under visible-light irradiation for about 2 h, the activated ReS2 nanosheets electrocatalyst performs highly enhanced catalytic activity, with an onset potential decreasing from 170 to 88 mV and a long stability over 10 h. It is worth noting that only a small overpotential of 116 mV is required to afford the current density of 10 mA cm −2, which is the highest activity to date for ReS2 electrocatalysts and much better than most transition-metal dichalcogenide materials electrocatalysts. Ex-situ transmission electron microscopy (TEM) and inductively coupled plasma emission spectrometer (ICP) examinations demonstrate that the performance improvement is attributed to the defect introduction during the visible-light assisted pre-electrolysis process involving the rhenium atoms vacancies on the basal planes and the lattice fringes of ReS2 . Theoretical calculations further confirm that the abundant Re atoms vacancies with lower Gibbs free energy for H adsorption activate the inert basal plane as highly active sites for hydrogen evolution. Graphical abstract: Ion-vacancy defects induced by visible-light irradiation are demonstrated both experimentally and theoretically as active sites for enhanced hydrogen generation of ReS2 nanosheets. The activated electrode shows the significant current density of 10 mA cm −2 at remarkably low overpotential of 116 mV, which is as far as we know the best ReS2 electrocatalyst reported to date.fx1 Highlights: The visible-light assisted pre-electrolysis are employed to introduce ion-vacancy defects. Ex-situ TEM and ICP investigations reveal the evolution process of defect-rich ReS2 nanosheets. The defect-rich electrode exhibits the best HER behavior for ReS2 electrocatalysts reported to date. The contributions of different ion vacancies are investigated by DFT calculations for the improved catalytic performance.